Sikh gurus, their religion and followers - Sher, Sher Singh, 1924- (Literary Sub-Committee, Shiromani Sikh Samaj, 1973)
Paper previously published in The world religions speak, revised and read in the special session of the Shiromani Sikh Samaj, Chandigarh on January, 21, 1973.